2016
DOI: 10.3390/ijerph13111114
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Electronic Cigarette Use from 2013 to 2015 and Reasons for Use among Finnish Adolescents

Abstract: Electronic cigarettes are quite a new potential source of nicotine addiction among youth. More research is needed, particularly on e-liquid use and socioeconomic factors as potential determinants. We studied changes from 2013 to 2015 in adolescent e-cigarette awareness and ever-use, types of e-liquids, and determinants in Finland. In 2015, we studied weekly use and reasons for ever-use. Data were from two national surveys of 12-18-year-old Finns (2013, n = 3535, response rate 38%; 2015, n = 6698, 41%). Descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 38 publications
8
48
2
2
Order By: Relevance
“…Medium nicotine content was found to have the opposite effect of low nicotine content. They also found that younger non-smokers preferred no nicotine or low nicotine e-cigarettes while smokers preferred medium and high nicotine e-cigarettes [ 22 ], echoing the findings of another study in this area [ 37 ]. Another study also found smokers and heavier e-cigarettes users tended to prefer nicotine [ 48 ].…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Medium nicotine content was found to have the opposite effect of low nicotine content. They also found that younger non-smokers preferred no nicotine or low nicotine e-cigarettes while smokers preferred medium and high nicotine e-cigarettes [ 22 ], echoing the findings of another study in this area [ 37 ]. Another study also found smokers and heavier e-cigarettes users tended to prefer nicotine [ 48 ].…”
Section: Resultsmentioning
confidence: 61%
“…Nicotine strength depends on e-cigarette type and varies widely, for example, from 0.27 to 2.91 mg/15 puffs [ 26 ]. Nineteen studies addressed consumer preference for nicotine and/or the interaction of nicotine with flavors [ 16 , 22 , 24 , 28 , 29 , 33 , 37 , 42 , 43 , 46 48 , 50 , 53 56 , 65 , 70 ]. One study showed that almost all e-cigarettes sold in most U.S. retail outlets (excluding vapor shops and online ones) contained nicotine [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of three studies examining current use, two studies found potentially positive impacts (one from Finland examining use by education [48], and another from Ireland examining use by neighbourhood deprivation [49]) while a third study (from the US) found unclear impacts by education [50]. For e-cigarette ever use, the first two studies showed unclear findings [48,49], as did a fourth study from France [51]. A fifth study (from Canada) found potentially positive impacts for ever use [52].…”
Section: Young Peoplementioning
confidence: 99%
“…This figure is lower than reported in Ireland among young people 16 -17 years old (23.8%) and in Poland among students aged 15 -19 years (62.1%) [22,23]. In Finland, 17.4% of adolescents had tried e-cigarettes in 2013, and 25.0% in 2015 [24]. The prevalence of e-cigarette use in the last 30 days was significantly higher among young males than females.…”
Section: Discussionmentioning
confidence: 68%